State regulation of venture financing of innovative activity - L. V. Prigoda (Новые технологии, 2017)
The author analyze the peculiarities of venture financing of innovative activity in the current economic conditions, note the essential role of state support for this field of activity, highlight the problems of the domestic system of state support for the development of venture financing of innovation activities.